(untitled) (Anclajes, 2015)
In Dos partidos en lucha (1875), and especially in La bolsa de huesos (1896), Eduardo Holmberg configures fictional narrations in which Darwinian theories and the contemporary debates and dilemmas of science acquire a significant centrality. In both cases, and in addition to an emphatic adherence to Darwinism and a clear apology for the scope of scientific practice, it is possible to detect a problematization of the institutional place of science, its feasible connections with the society and politics, and its role within the state structure. As a correlate, both narrations reveal tensions around and reformulations of one of their central axes, which is also central to the work of Charles Darwin: the modes of thinking, emphasizing or relativizing the link between human life and animal life. The aim of this paper is to address the interaction between these two issues in Holmberg’s fictions, through a contrastive textual analysis that contemplates the cultural context of the period.